2023
DOI: 10.1093/infdis/jiad114
|View full text |Cite
|
Sign up to set email alerts
|

Rifabutin-Containing Triple Therapy Versus Bismuth Quadruple Therapy for Helicobacter pylori Rescue Treatment: A Multicenter, Randomized Controlled Trial

Abstract: Background To compare the efficacy and safety of rifabutin-containing triple therapy with bismuth quadruple therapy for rescue treatment of Helicobacter pylori (H. pylori). Methods This was a non-inferiority study trial of H. pylori treatment for subjects who had failed at least two prior treatments. Subjects were randomly assigned to receive rifabutin triple therapy with 14-day esomeprazole (20 mg bid), amoxicillin (1.0 g bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In a study conducted in China, 364 patients were divided into two groups: the TT group (treated with 20 mg esomeprazole, 1000 mg amoxicillin, and 150 mg rifabutin, twice daily) and the BQT group (treated with 20 mg esomeprazole, 220 mg bismuth twice daily, along with 400 mg metronidazole, and 500 mg tetracycline four times daily). The results demonstrated that the therapeutic efficacy of the TT group was comparable to that of the BQT group (ITT analysis: 89.0% vs. 89.6%, p = 0.866; PP analysis: 94.0% vs. 95.3%, p = 0.602) 65 …”
Section: The Application Of Susceptibility Testingmentioning
confidence: 85%
See 1 more Smart Citation
“…In a study conducted in China, 364 patients were divided into two groups: the TT group (treated with 20 mg esomeprazole, 1000 mg amoxicillin, and 150 mg rifabutin, twice daily) and the BQT group (treated with 20 mg esomeprazole, 220 mg bismuth twice daily, along with 400 mg metronidazole, and 500 mg tetracycline four times daily). The results demonstrated that the therapeutic efficacy of the TT group was comparable to that of the BQT group (ITT analysis: 89.0% vs. 89.6%, p = 0.866; PP analysis: 94.0% vs. 95.3%, p = 0.602) 65 …”
Section: The Application Of Susceptibility Testingmentioning
confidence: 85%
“…The results demonstrated that the therapeutic efficacy of the TT group was comparable to that of the BQT group (ITT analysis: 89.0% vs. 89.6%, p = 0.866; PP analysis: 94.0% vs. 95.3%, p = 0.602). 65 However, it is important to note that not all low-resistance antibiotic TTs are equally effective. A meta-analysis pooling data from 23 studies on semi-synthetic tetracycline found eradication rates in TT to be lower than 70% in both ITT and PP analyses.…”
Section: Susceptibility Testing In Ttmentioning
confidence: 99%
“…It was noted that isolates with amoxicillin resistance were less likely to be successfully eradicated using rifabutin-based treatment, with a drop in eradication from 94.8% to 66.7%. It did not have the same effect on those in the bismuth group [ 50 ].…”
Section: Management: Treatmentmentioning
confidence: 99%